2018
DOI: 10.1056/nejmoa1717002
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib in Patients with Advanced and Progressing Hepatocellular Carcinoma

Abstract: Among patients with previously treated advanced hepatocellular carcinoma, treatment with cabozantinib resulted in longer overall survival and progression-free survival than placebo. The rate of high-grade adverse events in the cabozantinib group was approximately twice that observed in the placebo group. (Funded by Exelixis; CELESTIAL ClinicalTrials.gov number, NCT01908426 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
1,741
6
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,888 publications
(1,924 citation statements)
references
References 30 publications
32
1,741
6
22
Order By: Relevance
“…For example, a recently published trial of rituximab plus lenalidomide versus rituximab plus chemotherapy reported in its abstract conclusion that “the safety profile differed in the two groups.”5 Although this statement is not very informative, it is at least an objective description and readers can look at the adverse effect profiles and frequencies for themselves. Another trial abstract concluded: “The rate of high-grade adverse events in the cabozantinib group was approximately twice that observed in the placebo group.”12…”
Section: Better Reportingmentioning
confidence: 99%
“…For example, a recently published trial of rituximab plus lenalidomide versus rituximab plus chemotherapy reported in its abstract conclusion that “the safety profile differed in the two groups.”5 Although this statement is not very informative, it is at least an objective description and readers can look at the adverse effect profiles and frequencies for themselves. Another trial abstract concluded: “The rate of high-grade adverse events in the cabozantinib group was approximately twice that observed in the placebo group.”12…”
Section: Better Reportingmentioning
confidence: 99%
“…The median overall survival (OS) was substantially longer in CPA compared with CPB patients (9.5 months [95% CI, 8.5-14.8 months] vs 3.2 months [95% CI, 2.7-6.0 months]). [14][15][16] There are limited data to guide the dosing of these agents in patients with CPB or greater hepatic dysfunction. [7][8][9][10][11][12][13] No starting dose adjustment is indicated for CPB liver dysfunction in the drug label.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hepatitis B continues to drive the majority of the global burden of HCC, especially in southeast Asia and sub-Saharan Africa. After the development of sorafenib, 8,9 4 agents have demonstrated improved outcome data: lenvatinib 10 in the first-line and regorafenib, 11 cabozantinib, 12 and ramucirumab 13 after first-line disease progression. Despite those curative efforts, the majority of patients ultimately will experience a recurrence of their disease.…”
Section: Introductionmentioning
confidence: 99%